Strategi Pengembangan Industri Pengolahan Makanan Khas Bengkulu di Kota Bengkulu - Tiara Windiana; Novi Tri Putri (Convergence: The Journal of Economic Development, 2021)
The objectives of this research are: (1) Knowing the internal and external factors in the development of small industry of Bengkulu typical food processing in Bengkulu City and (2) Formulating a development strategy to increase the growth of small industry of Bengkulu typical food processing in Bengkulu City. This research is a type of quantitative descriptive research. The types of data used are primary and secondary data obtained from the Central Statistics Agency of Bengkulu Province in 2016-2020 and the distribution of questionnaires. The data analysis method used is descriptive analysis and SWOT analysis. Based on the results of data analysis, it is found that the strategy that can be carried out for the business of developing Bengkulu specialties is the W-O strategy, namely: (a) Making regulations on the preservation of regional culture; (b) Build special food business centers; (c) Facilitation and support for business capital from the relevant agencies/agencies; and (d) Conducting bazaars or events for regional and national culinary specialties. Keywords: Strenght, Weakness, Opportunity, Threats and Strategy